2021
DOI: 10.1186/s12913-021-06955-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring clinicians’ experiences and perceptions of end-user roles in knowledge development: a qualitative study

Abstract: Background End-user involvement in developing evidence-based tools for clinical practice may result in increased uptake and improved patient outcomes. Understanding end-user experiences and perceptions about the co-production of knowledge is useful to further the science of integrated knowledge translation (iKT) – a strategy for accelerating the uptake and impact of research. Our study had two main objectives: (1) explore end-user (clinician) experiences of co-producing an evidence-based practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Our study is situated within a larger project, whereby end-users co-developed an evidence-based care pathway to facilitate the clinical management of shoulder pain in adults. In a previous publication, we describe clinicians’ experiences of co-producing the care pathway and their perceptions of participating in knowledge tool development [ 21 ]. Collectively, our findings provide a guide for engaging clinicians in integrated knowledge translation (iKT) endeavors and co-producing clinical resources [ 45 – 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is situated within a larger project, whereby end-users co-developed an evidence-based care pathway to facilitate the clinical management of shoulder pain in adults. In a previous publication, we describe clinicians’ experiences of co-producing the care pathway and their perceptions of participating in knowledge tool development [ 21 ]. Collectively, our findings provide a guide for engaging clinicians in integrated knowledge translation (iKT) endeavors and co-producing clinical resources [ 45 – 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used the Consolidated Criteria for Reporting Qualitative Research (COREQ) to guide this study’s conduct and reporting. The methods of this study have been previously reported in a related study [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such power imbalances within the intersection of healthcare and research, particularly between those receiving and delivering such services and those designing such services, have been widely reported [ 12 , 13 ]. There are concerted efforts within health service development, health research and health research funding, to rectify this power imbalance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians and patients without training in interpreting NMA results would not likely be able to use this information directly for treatment decisions. Stakeholder engagement in the website design process could improve uptake and dissemination of NMA results [ 11 ].…”
Section: Introductionmentioning
confidence: 99%